RNAScope in situ Hybridization as a Novel Technique for the Assessment of c-KIT mRNA Expression in Canine Mast Cell Tumor - De Biase, Davide; Prisco, Francesco; Piegari, Giuseppe; Ilsami, Arianna; d'Aquino, Ilaria; Baldassarre, Valeria; Zito Marino, Federica; Franco, Renato; Papparella, Serenella; Paciello, Orlando (Frontiers in Veterinary Science, 2021)
RNA has recently emerged as a novel biomarker, as it is an ideal indicator of the dynamic genetic expression changes in a cell. RNAScope is a commercially available In Situ Hybridization assay for the detection of RNA in formalin-fixed paraffin-embedded tissue. In this work we describe, the use of RNAScope as a sensitive and specific method for the evaluation of c-KIT mRNA in canine Mast Cell Tumor. We investigated the expression of c-KIT mRNA with RNAscope in 60 canine MCTs comparing it with the histologic grade and KIT immunohistochemical expression patterns. Our results showed an overall good expression of c-KIT mRNA in neoplastic cells if compared with control probes. We also observed a statistically significant correlation between histologic grade and c-KIT mRNA expression. No correlations were found between KIT protein immunohistochemical distribution pattern and c-KIT mRNA expression or histologic grade. Our results provide a reference basis to better understand c-KIT mRNA expression in canine MCTs and strongly encourage further studies that may provide useful information about its potential and significant role as a prognostic and predictive biological marker for canine MCTs clinical outcome.